EARLY LEARNINGS FROM A LARGE PALLIATIVE CARE COMPARATIVE EFFECTIVENESS TRIAL. (11th November 2018) - Enguidanos, S; Rahman, A; Mack, W
Abstract: Although early studies of home-based palliative care (HBPC) demonstrate strong evidence of improved patient outcomes and reduced costs, this model of care has experienced limited transfer outside of managed care environments. Under a contract from Patient Centered Outcomes Research Institute, we are conducting a pragmatic comparative effectiveness trial of HBPC versus enhanced usual care across 10 medical groups in California, enrolling more than 1, 000 patients and their caregivers. In this session we present lessons learned in engaging a myriad of stakeholders: patients and caregivers, primary care physicians, medical group administrators, and HBPC providers. Additionally, we describe challenges to participant enrollment and mechanisms undertaken to overcome obstacles to patient and caregiver enrollment. We also discuss the role of patient and caregiver stakeholders in our study and in overcoming our barriers to engagement.